PENGEMBANGAN MODUL ELEKTRONIK MOTIVASI BELAJAR SISWA DENGAN MENGGUNAKAN APLIKASI KVISOFT FLIPBOOK BERBASIS ETNHOKONSTRUKTIVISME - Qalbi Shanaz Anandari; Eka Feri Kurniawati; Marlina Marlina; Suci Okta Piyana; Lia Gusti Melinda; Rizka Meidiawati; Muhammad Rizky Fajar (PEDAGOGIK : JURNAL PENDIDIKAN, 2019)
Technological progress is inseparable from the success of an education. In the process of learning technology it is important to be integrated in teaching materials. However, while still supporting schools that do not have teaching materials using technology. Therefore, development research is carried out that makes teaching materials by utilizing technology that develops electronic modules. This type of research is a research development developed by Sugiyono. The trial was conducted by giving questionnaires to 21 students of Sridadi 55 / I public elementary schools. Based on the results of research and development figures obtained 85.6% with the category "Good" on the motivation of students in using electronic modules in the learning process